PCLAB physics computer laboratory - Loya, Alvin P. (1998)
Physics Computer Laboratory (PC Lab) is software designed to simulate high school Physics laboratory experiments. Its development is being supervised by the Physics Education Group of the Institute for Science and Mathematics Education development of the University of the Philippines, Diliman. PC Lab serves two primary purposes. First, it will act as an interactive environment wherein the student can perform simulated Physics laboratory experiments. To this end, PC Lab offers several benefits over the conventional way of performing laboratory experiments. First, no money is required for actual laboratory equipment. Second, maximum control may be imposed over factors affecting the experiments' results. Third, precision and accuracy in measurements will be ensured. Fourth, no time constraints will be imposed. Fifth, experiments may be repeated at various stages. And finally, no experiment related accidents and damages will occur. Another purpose of PC Lab is to act as a teaching tool which can be used by Physics teachers in pre-laboratory and post-laboratory lectures. Compared to other teaching media, PC Lab offers the advantage of allowing the instructor to perform the experiment while discussing it in front of the students. The PC Lab report is divided into two main parts. The first part is devoted to the discussion of the art and science of computer simulation; it is composed primarily of definitions of pertinent concepts involved in system simulation. The second part is devoted to the description of the Physics laboratory experiments which PC Lab will simulate in the computer, it contains specifications of the experiments' materials, instruments, objectives, and general procedures. The design and implementation part of PC Lab's technical report, is included here as Appendix D. The developers of PC Lab are hopeful that the software would serve the humble purpose of helping our schools educate students who are eager to learn. They are also hoping that the release of this software will make educational institutions aware of the fact that the learning process can be aided through the use of computers. Particularly the powerful personal computers that we have a present.